2013
DOI: 10.1007/s12282-013-0465-3
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver variability of ultrasound elastography and the ultrasound BI-RADS lexicon of breast lesions

Abstract: Elasticity score showed a higher level of interobserver agreement for the diagnosis of breast lesions than BI-RADS lexicons and final category.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 13 publications
0
33
1
2
Order By: Relevance
“…SWE is differentiated from conventional static elastography in automatically induced mechanical vibration via the radiation force of US beams (1,2,7,8,22). So, it less affected by the individual compression skills than static elastography (1,2,7,8,22).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…SWE is differentiated from conventional static elastography in automatically induced mechanical vibration via the radiation force of US beams (1,2,7,8,22). So, it less affected by the individual compression skills than static elastography (1,2,7,8,22).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported intra-and interobserver reproducibility of SWE (7,9,22). Cosgrove et al (9) reported that intraobserver reliability for maximum and mean elasticity was almost perfect (ICC = 0.84 and 0.87) and was substantial for the ratio of mass-to-fat elasticity (ICC = 0.77).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations